Preliminary Study on World-Wide Implementation of Adaptive Content Distribution Network - Miyauchi, Yuta; Matsumoto, Noriko; Yoshida, Norihiko; Shimokawa, Toshihiko (Electronic Communications of the EASST, 2011)
A conventional Content Distribution Network (CDN) has a static structure, therefore, it is not an effective solution to a flash crowd, that is a rapid increase in server load caused by a sudden access concentration. We have proposed an adaptive CDN, FCAN (Flash Crowds Alleviation Network), which changes its structuredynamically against flash crowds. In this paper, we verify FCAN on a real world-wide network. Through some experiments, we confirmed that FCAN achieves load distribution effectively.